Respuesta :

from the third equation      2z=-2x+4
                                          z=-x+2
plug into the second equation    -4+4y+5(-x+2)=7
                                                   -4+4y-5x+10=7
                                                   4y-5x=1
                                                    y=5/4x+1/4
plug both of these into the first equation     x+y+z=8
                                                                    x+5/4x+1/4+(-x+2)=8
                                                                     5/4x+2.25=8
                                                                      5/4x=5.75
                                                                           x=4.6
now plug back into the substitution equations.
z=-x+2= -4.6+2= -2.6
y=5/4x+1/4=5.75+1/4=6

the answer is (4.6, 6, -2.6)

Answer:

In Point Form: (x,y,z)= (3,6,-1)

In Equation Form: x=3, y=6, z=-1

Step-by-step explanation:

1) Solve for x

           2x+2z=4 (Subtract 2z from both sides)

           -2z  -2z

           2x= 4-2z  (Divide 2 from both sides)

           /2      /2

           x=2-z

2) Substitute 2-z for x in

                       -x-y-z=-8

                       -(2-z)-y-z=-8

                       -2+z-y-z=-8  (Combine Like Terms)

                       -2-y=-8 (Add 2 to both sides)

                       +2     +2

                       -y=-6  (Divide -1 from both sides)

                       /-1   /-1

                       y=6

3) Substitute 2-z for x & 6 for y in

                          -4x+4y+5z+=7

                          -4(2-z)+4(6)+5z=7  (Get rid of parentheses)

                          -8+4z+24+5z=7   (Combine Like Terms)

                          9z+16=7  (Subtract 16 from both sides)

                               -16  -16

                          9z+=-9  (Divide 9 from both sides)

                          /9     /9

                          z=-1

4) Now find x by substituting -1 for z in

                                          x=2-z

                                          x=2-(-1)  

                                          x=2+1

                                          x=3  

Therefore the answer is:

In Point Form: (x,y,z)= (3,6,-1)

In Equation Form: x=3, y=6, z=-1

ACCESS MORE